Role of Topoisomerase IIβ in the Expression of Developmentally Regulated Genes - Lyu, Yi Lisa (American Society for Microbiology, 2006)
Mice lacking topoisomerase IIβ (TopIIβ) are known to exhibit a perinatal death phenotype. In the current study, transcription profiles of the brains of wild-type and top2β knockout mouse embryos were generated. Surprisingly, only a small number (1 to 4%) of genes were affected in top2β knockout embryos. However, the expression of nearly 30% of developmentally regulated genes was either up- or down-regulated. By contrast, the expression of genes encoding general cell growth functions and early differentiation markers was not affected, suggesting that TopIIβ is not required for early differentiation programming but is specifically required for the expression of developmentally regulated genes at later stages of differentiation. Consistent with this notion, immunohistochemical analysis of brain sections showed that TopIIβ and histone deacetylase 2, a known TopIIβ-interacting protein, were preferentially expressed in neurons which are in their later stages of differentiation. Chromatin immunoprecipitation analysis of the developing brains revealed TopIIβ binding to the 5′ region of a number of TopIIβ-sensitive genes. Further studies of a TopIIβ-sensitive gene, Kcnd2, revealed the presence of TopIIβ in the transcription unit with major binding near the promoter region. Together, these results support a role of TopIIβ in activation/repression of developmentally regulated genes at late stages of neuronal differentiation.